Effect of environmental exposure on the cooling rate of asphalt mixtures - Badruddin, I.; Abdul Hassan, N.; Mahmud, M. Z. H.; Ismail, S.; Putra Jaya, Ramadhansyah; Oleiwi Aletba, S. R.; Mohd Rosli, Hainin (IOP Science, 2021)
Temperature is one of the major factors that affect the compactability and mechanical performance of asphalt pavement. Therefore, the cooling rate variability of asphalt due to various surrounding conditions and aggregate surface areas is crucial to achieving proper compaction. This study focused on the effect of environmental exposure on the cooling rate and available time for compaction of the asphalt mixtures (AC10 and AC14). Several factors, such as base and ambient temperatures, daytime and nighttime, solar flux, and wind speed, were considered in the evaluation of the cooling curve. A few loose samples were prepared and grouped as covered (with canvas) and uncovered during the monitoring process. The time and temperature of both samples were monitored during the day and night, starting after the mixing process and ending at 80 °C. Results reveal that the cooling rate of asphalt mixtures is undoubtedly affected by the surrounding factors. The use of canvas and coarse aggregate gradation could retain the heat and minimize the wind and solar flux effects, thus increasing the available time for compaction or lengthening the cooling time. In addition, the cooling rate tends to increase during nighttime compared with daytime exposure.